The Effect of Lavender Aromatherapy on Postpartum Blues of Primipara Mothers : A Scoping Review - Imelda Rismayani Gampur; Moch Anwar; Herlin Fitriani Kurniawati (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2022)
Background: The concept of health technology assessment is described in health studies as promotion, prevention, screening, comparison, treatment, rehabilitation and care for a long time. Documentation of the incidence of postpartum blues is still rarely done through health care facilities in Indonesia. Based on previous research, the incidence of postpartum blues is in the range of 74.4%. This situation needs attention because 10-15% could potentially develop into postpartum depression. Lavender aromatherapy has an active ingredient, namely linalool which has a relaxing effect so that it can relieve insomnia, anxiety, and depression. Purpose: This Scoping Review was to evaluate the influence of lavender aromatherapy towards postpartum blues on primipara mothers. Method: Scoping Review which adapts Arskey and O'Malley framework using databases from Pubmed, ScienceDirect, ProQuest. Selection of article studies with Prism Flowcharts, mapping of charting data and descriptions of article search flow, compilation, summary and reporting of results as well as discussions with Critical Appraisal. The tool used in the scoping review is the Mixed Method Appraisal Tool (MMAT). Conclusion: The research gap found was the effect of lavender aromatherapy as an alternative non-pharmacological method that was effective on the incidence of postpartum blues in postpartum mothers.